Long‐Term Incidence of Dementia Following Transient Ischemic Attack: A Longitudinal Cohort Study - Vasileios‐Arsenios Lioutas; Gina Peloso; Jose Rafael Romero; Hugo Aparicio; Mitzi Gonzales; Amy Werry; Dibya Himali; Jayandra Himali; Ayantika Banerjee; Saptaparni Gosh; Vasan S. Ramachandran; Alexa Beiser; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The association between transient ischemic attack (TIA) and dementia is incompletely characterized. Determining the cognitive sequalae of TIA is important as it can function as an early warning sign or additional risk factor for dementia. We sought to determine the long‐term incidence of post‐TIA dementia and examined whether TIA prompts changes in vascular risk factors. Methods Nested matched longitudinal cohort study within the community‐based Framingham Heart Study. A prospectively collected sample of participants without dementia or transient ischemic attack were matched on age and sex (5:1) to participants with first incident TIA >60 years. The primary outcome of interest was the 20‐year incidence of all‐cause dementia. Results The study matched 297 participants with TIA, 141 (47%) men, mean age 72.7±7.7 years, with 1485 controls without TIA. People with TIA were more likely to have hypertension, coronary heart disease, and atrial fibrillation. Over a median of 8.9 years of follow up, 57 (19%) participants with TIA and 353 (24%) controls without TIA developed dementia (hazard ratio [HR], 0.93 [95% CI, 0.71–1.24], P=0.63). Adjusting for stroke and accounting for the competing risk of death did not alter this association. Participants with TIA were more likely to have a reduction in the frequency of smoking (18% to 11%, P=0.025), an increase in anticoagulant use from 3% to 18%, (P=0.0005), and a marginal increase in aspirin use (46% to 61%, P=0.052). Conclusions We found no significant difference in dementia incidence over a 20‐year follow‐up period compared with matched TIA‐free controls. Our findings suggest that TIA prompts treatment changes and behavioral shifts that lower cardiovascular risk. Whether these are sufficient to mitigate subsequent dementia risk remains to be tested in prospective randomized studies.